Fundamental and emerging insights into innate and adaptive immunity in inflammatory bowel diseases - Monteleone, Giovanni; Calisi, Carlo; Salvatori, Silvia; Marafini, Irene (Frontiers in Immunology, 2025)
Inflammatory bowel diseases (IBD) are chronic and disabling disorders of the gastrointestinal tract of unknown aetiology, in which the pathologic process is triggered by multiple environmental and genetic factors that activate an excessive innate and adaptive immune response against luminal antigens. In recent years, great progress has been made in the identification of factors/mechanisms underlying the amplification of the key immune steps in IBD tissue, and this has facilitated the development of several immune-related biotherapeutic compounds that have largely improved the management of the more severe forms of IBD. However, nearly half of these patients are refractory or intolerant to novel immunotherapeutics, indicating the need for further characterization of the IBD-associated detrimental immune response to develop new therapeutics. In this article, we review the available evidence about the contribution of innate and adaptive immune cells in the development of intestinal tissue damage. We also discuss the more recent findings in the field of IBD-associated immunity, which might help identify novel pathways to be manipulated for therapeutic purposes.